Balancing state sovereignty and the protection of human rights: a case study on the impact of the requirements of state consent and the exercise of political will on the functioning of the human rights systems of the African Union and the Southern African Development Community - Kunaka, Sheryl (Department of Public Law, 2022)
In recent decades, achieving the goal of the global protection of human rights has been approached most commonly through multilateralism. States have since abandoned notions of self-reliance in favour of interdependency and collaboration, leading to a proliferation of international, regional, and sub-regional multilateral organizations. However, the definition of ‘multilateralism' restricts the application of the legal frameworks of these organizations to sovereign states that have voluntarily consented to be bound by the obligations contained therein. State consent and political will drive multilateralism, and the requirement of voluntariness in these forms has been utilised as a means of respecting the internationally recognized legal principle of state sovereignty. Consequently, voluntariness has impacted the effective functioning of organizations such as the African Union (‘AU') and the Southern African Development Community (‘SADC'). This thesis proposes that the less significant the impact of voluntariness is on a regional or sub-regional human rights system, the more effective it will be in its role of protecting human rights. This thesis provides practical ways of lessening the impact of voluntariness, in order to strengthen the human rights legal frameworks of the AU and the SADC; and to improve the functioning of their respective compliance mechanisms. This thesis achieves the aforementioned by drawing from the systems' European and African regional and sub-regional counterparts.